Effect of caloric restriction on oxidative markers - Skrha, Jan (Advances in clinical chemistry, 2009)
Caloric restriction is associated with a decreased level of oxidative stress. Reactive oxygen species (ROS) generated predominantly in mitochondria are attenuated by decreased caloric intake. On the other hand, antioxidative mechanisms are frequently accelerated by increased gene expression or activities of antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase, paraoxonase, etc.). Measurement of different oxidative stress markers in relationship to caloric restriction is therefore important in experimental as well as clinical studies. Estimation of ROS in tissues and fluids is typically performed by measurement of oxidant products (i.e., malondialdehyde, F-2-isoprostanes, nitrotyrosine) and markers of antioxidant system (enzymes, glutathione, alpha-tocopherol, ascorbic acid, ubichinone, etc.). Because both components are critical to objectively understand the oxidative stress state, tangible biochemical data is required in order to comprehensively elucidate pathobiologic mechanisms and potential therapeutic regimes involving lifestyle changes that include caloric restriction or moderate physical activity.
Keywords: Humans; biologické markery; lidé; kalorická restrikce; Biomarkers; Caloric Restriction